Assessment of the phenology, silage yield and quality of spring maize (Zea mays)in different crop rotations - BRAR, NAVJOT SINGH; KAUR, SIMERJEET; KINGRA, P K; HUNDAL, JASPAL SINGH (The Indian Journal of Agricultural Sciences, 2025)
In north-western India, maize (Zea mays L.) is mainly grown in spring season for silage making. Sowing time of spring maize in different rice (Oryza sativa L.) and maize-based crop rotations varies, and it affects the yield and quality of silage. The present experiment was conducted during 2020–21 and 2021–22 at Punjab Agricultural University, Ludhiana, Punjab with four crop rotations i.e. maize–toria (Brassica rapa ssp. oleifera)-spring maize (silage); rice (Oryza sativa L.)–barley (Hordeum vulgare L.) (silage)–spring maize (silage); rice–wheat (Triticum aestivum L.) (silage)–spring maize (silage) and maize–rapeseed (Brassica napus L.)–spring maize (silage) to evaluate the spring maize silage yield and quality in randomised complete block design (RCBD) with three replications. Sowing of spring maize was undertaken from 8th February to 19th March in different crop rotations and harvested at milk stage for silage making. Spring maize grown in maize–toria–spring maize took greater number of days for reaching all phenological stages. During 2021, heat use efficiency (HUE) was higher in maize–toria–spring maize, was similar with rice–barley–spring maize and rice–wheat–spring maize. However, during 2022, maize–toria–spring maize recorded higher HUE and better silage quality than all other treatments. Higher silage yield of spring maize was recorded in maize–toria–spring maize, was similar to rice–barley–spring maize but higher than rice–wheat–spring maize and maize–rapeseed–spring maize rotations during both years. The delayed sowing altered the phenological development of maize, resulted in reduced silage yield and quality. Further, heat wave in northern India during March 2022 resulted in 24–28% reduction in silage yield in four crop rotations during 2022 than 2021. Results indicated that maize–toria–spring maize and rice–barley–spring maize rotations are most suitable for achieving high-quality spring maize silage production.